Metal‐Organic Fragments with Adhesive Excipient and Their Utilization to Stabilize Multimetallic Electrocatalysts for High Activity and Robust Durability in Oxygen Evolution Reaction - Choi, Won Ho; Kim, Keon‐Han; Lee, Heebin; Choi, Jae Won; Park, Dong Gyu; Kim, Gi Hwan; Choi, Kyung Min; Kang, Jeung Ku (Advanced science, 2021)
Multimetallic electrocatalysts have shown great potential to improve electrocatalytic performance, but their deteriorations in activity and durability are yet to be overcome. Here, metal‐organic fragments with adhesive excipient to realize high activity with good durability in oxygen evolution reaction (OER) are developed. First, a leaf‐like zeolitic–imidazolate framework (ZIF‐L) is synthesized. Then, ionized species in hydrogen plasma attack preferentially the organic linkers of ZIF‐L to derive cobalt–imidazole fragments (CIFs) as adhesive excipient, while they are designed to retain the coordinated cobalt nodes. Moreover, the vacant coordination sites at cobalt nodes and the unbound nitrogen at organic linkers induce high porosity and conductivity. The CIFs serve to stably impregnate trimetallic FeNiMo electrocatalysts (CIF:FeNiMo), and CIF:FeNiMo containing Fe contents of 22% and hexavalent Mo contents show to enable high activity with low overpotentials (203 mV at 10 mA cm−2 and 238 mV at 100 mA cm−2) in OER. The near O K‐edge extended X‐ray absorption fine structure proves further that high activity for OER originates from the partially filled eg orbitals. Additionally, CIF:FeNiMo exhibit good durability, as demonstrated by high activity retention during at least 45 days in OER. A strategy is developed to produce metal‐organic fragments allowing to stabilize multimetallic electrocatalysts in which a leaf‐like zeolitic–imidazolate framework is transformed into Co–imidazole fragments (CIFs) with unsaturated orbitals and dangling bonds as adhesive excipient. Fe, Ni, and Mo elements impregnated within CIFs, referred as CIF:FeNiMo catalysts, demonstrate high activity with low overpotentials (203 mV at 10 mA cm−2 and 238 mV at 100 mA cm−2) and robust durability with high activity retention (during at least 45 days) in oxygen evolution reaction.